Corrosion and tribocorrosion of hafnium in simulated body fluids. Issue 6 (26th December 2013) - Rituerto Sin, J.; Neville, A.; Emami, N.
Abstract Hafnium is a passive metal with good biocompatibility and osteogenesis, however, little is known about its resistance to wear and corrosion in biological environments. The corrosion and tribocorrosion behavior of hafnium and commercially pure (CP) titanium in simulated body fluids were investigated using electrochemical techniques. Cyclic polarization scans and open circuit potential measurements were performed in 0.9% NaCl solution and 25% bovine calf serum solution to assess the effect of organic species on the corrosion behavior of the metal. A pin‐on‐plate configuration tribometer and a three electrode electrochemical cell were integrated to investigate the tribocorrosion performance of the studied materials. The results showed that hafnium has good corrosion resistance. The corrosion density currents measured in its passive state were lower than those measured in the case of CP titanium; however, it showed a higher tendency to suffer from localized corrosion, which was more acute when imperfections were present on the surface. The electrochemical breakdown of the oxide layer was retarded in the presence of proteins. Tribocorrosion tests showed that hafnium has the ability to quickly repassivate after the oxide layer was damaged; however, it showed higher volumetric loss than CP titanium in equivalent wear‐corrosion conditions. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1157–1164, 2014.